Photocatalytic degradation characteristics of heterojunction SnO2-CuxO nanopowders of methylene blue under UV light - Eom, Kiryung; Yoo, Il Han; Kalanur, Shankara Sharanappa; Seo, Hyungtak (Korean Journal of Chemical Engineering, 2021)
p-n heterojunction was constructed using p-type Cupric oxide (CuO) and n-type Tin (IV) oxide (SnO2) nanoparticles using chemical synthesis and annealing method. The synthesized SnO2-CuO nanoparticles were characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), etc. The methylene blue (MB) degradation ability of the synthesized SnO2-CuO nanocomposite was investigated under UV illumination. Compared to the undoped SnO2, the SnO2-CuO p-n heterojunction exhibited enhanced MB degradation capability due the effective separation of electron-holes pair that suppresses the recombination. Based on the experimental results, the charge dynamics and the probable dye degradation mechanism via SnO2-CuO nanoparticles was proposed.
Keywords: CuO; Heterojunction; Nanoparticles; Photocatalyst; SnO2